Efektivitas model pembelajaran tipe talking chips dalam peningkatan hasil belajar siswa pada mata pelajaran akidah akhlak di sekolah menengah pertama Al-Irsyad Surakarta - Alimatur Rofi'ah; Joko Subando; Agus Fatuh W (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This study aims, 1) To determine student learning outcomes after using the cooperative learning model of the talking chips type in the subject of moral ethics at SMP Al-Irsyad Surakarta. 2) To find out the results of student learning after using conventional learning models in the subject of aqidah morals at SMP Al-Irsyad Surakarta. 3) To find out whether there is a significant difference between student learning outcomes using the talking chips cooperative learning model and student learning outcomes using conventional learning models in the subject of aqidah morals at SMP Al-Irsyad Surakarta. This type of research is quantitative research. The results of the study include, 1) The average value of students after using the talking chips type of cooperative learning model is 82.92 and is in the medium category. 2) The average student score after using the conventional learning model is 64 and is in the medium category. 3) There is a significant difference between the learning outcomes of students who use the cooperative learning model of the talking chips type and the learning outcomes of students who use conventional learning models in the subject of aqidah morals at SMP Al-Irsyad Surakarta by using the Independent Sample t-test that the value is significant (2-tailed) is 0.001 <0.05, so it is significant. The average increase in learning outcomes using conventional methods to learning outcomes using the talking chips method is 18.92.